INDONESIA–ANGOLA TRADE AND INVESTMENT POTENTIAL: A PRODUCT CLASSIFICATION MODEL USING REVEALED COMPARATIVE ADVANTAGE AND CONSTANT MARKET SHARE ANALYSIS - Sinta Rindiani, Nadia; Sjahril Sabaruddin, Sulthon; As'adur Rofiq, Mochammad (KAIRÓS, revista de ciencias económicas, jurídicas y administrativas, 2026)
Indonesia and Angola have cordial diplomatic relations, but the economic cooperation is limited. This study uses the RCA-CMSA Product Classification Model to identify potential trade and investment opportunities. The study reveals that Indonesian export opportunities include palm oil and ferro alloys; meanwhile, Angolan export opportunities include petroleum and gas. In the investment sphere, Indonesian potential inbound investment from Angola includes cocoa and coffee. There is no suggested Indonesian outbound investment in Angola, but it could refer to the investment offer by AIPEX and Angola's SEZs to support Angola’s economic diversification agenda. The study also suggests extending technical cooperation and establishing the Indonesia-Angola PTA to elevate the economic relations.